(untitled) (Journal of Economic Research & Business Administration, 2015)
The questions of increasing innovation activity of enterprises of Kazakhstan in the context of globalization, evaluated and determined constraints enterprise innovation, offers advice to encourage and enhance innovative activity of industrial enterprises. The results of the SWOT-analysis conducted by the innovative activity of enterprises: advantages, disadvantages, opportunities and threats. Proposed priorities for improving the innovation activity of the industrial enterprises, as well as the main stages of the innovation efficiency of the enterprise, such as the collection and processing of the necessary information, documents, analysis of indicators, market research on the introduction of an innovative project. Grouped economic indicators for assessing implementation of the innovative project: to improve the quality and competitiveness of the goods, lower commodity prices, increased output of commodity programs, development of new markets, improving the quality of goods and services, etc.